Review of Ukrainian, Slovakian and Serbian Municipal Waste Management: Comparative Study - Valenćiková, Marina (Видавництво Львівської політехніки, 2022)
The Carpathian Euroregion comprises of five countries: Poland, Slovakia, Hungary, Romania and Ukraine, as the Euroregion's fifth state, aspires to join the EU. As a result, we chose to compare Slovak Republic as an EU member state and Serbia and Ukraine as candidate countries. To support waste reduction and a circular economy, European law establishes waste management principles incorporated into national legislation across all EU member states. The key document of Slovakia is the Envirostrategy 2030, which sets a target of 60 % recycling and 10 % landfilling by 2030. In 2017, Ukraine's Cabinet approved a National Waste Management Strategy for the period up to 2030, and Serbia approved a Waste Management Program in the Republic of Serbia for the period 2022 - 2031; as a crucial aspect of the EU's new growth strategy to move the EU economy toward a sustainable economic model, the research article focuses on the European Green Deal and its effects on the countries under examination. This research paper's goal is to assess the state of Serbia, Slovakia, and Ukraine focusing on the waste situation in particular. While Ukraine and Serbia have enacted legislation requiring waste separation, this is only being implemented gradually in practice, and insufficient infrastructure is another issue. Slovakia has a slightly better situation due to its more advanced infrastructure.
Keywords: municipal waste management; circular economy; Ukraine; Slovakia; Serbia